The Reader's Digest illustrated book of cats. - Reader's Digest Association (Canada) (Montreal : Reader's Digest Association, 1992)
Presents information about cats including their history, anatomy, breeds, genetics, physiology, buying and caring for cats, exhibiting cats clubs and associations. Includes illustrations and photographs of many of the topics discussed.
Includes index.
Publishers Weekly.
Young adult
Keywords: Cat breeds; Cats; Cats